EVALUATION OF HEAVY METALS POLLUTION IN SOME SOILS FROM EGBEDI DUMPSITE AND ITS SURROUNDINGS IN OSOGBO, NIGERIA - Ogungbile, P.O.; Ajibare, A.O.; Enochoghene, A.E.; Ogunwale, T.O.; Sindiku, O.; Togunde, N. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study evaluates heavy metal pollution status in soils from the Egbedi dumpsite and its surrounding residential areas in Osogbo, Nigeria. Soil samples were collected at five distances (0 m, 200 m, 500 m, 1 km, and 1.5 km) from the site over three months, focusing on the concentrations of cadmium, chromium, cobalt, copper, iron, lead, manganese, and zinc. The samples were digested for their heavy metal concentration using aqua regia and analyzed through Flame Atomic Absorption Spectrophotometer. Quality assurance techniques adopted included blank determination, recovery analysis, and calibration of standards. Descriptive and inferential statistics were employed for data interpretations. Metal pollution assessment was conducted by employing mathematical models in terms of anthropogenic contamination factor, degree of contamination, element contamination index, metal contamination index, enrichment factor, geo-accumulation index, and pollution load index. The total metal concentrations for the three months varied from 0.01 mgkg-1 Pb to 268.40 mgkg-1 Fe. Pollution indices, including CF, ECI element, and PLI, confirmed severe anthropogenic contamination at the dumpsite, with a CF of 2.03 for Cd and an ECI of 1.03. The Cdeg and MCI were notably high, reaching 295.91 and 287.91, respectively. All the models showed that pollution statuses were in decreasing order of A>B>C>D>E across the sites. These findings underscore the urgent need for effective waste management strategies and regular monitoring to mitigate heavy metal pollution, its ecological and health impacts.